Mechanisms underpinning the permanent muscle damage induced by snake venom metalloprotease. - Harry F Williams; Ben A Mellows; Robert Mitchell; Peggy Sfyri; Harry J Layfield; Maryam Salamah; Rajendran Vaiyapuri; Henry Collins-Hooper; Andrew B Bicknell; Antonios Matsakas; Ketan Patel; Sakthivel Vaiyapuri (Public Library of Science (PLoS), 2019)
Snakebite is a major neglected tropical health issue that affects over 5 million people worldwide resulting in around 1.8 million envenomations and 100,000 deaths each year. Snakebite envenomation also causes innumerable morbidities, specifically loss of limbs as a result of excessive tissue/muscle damage. Snake venom metalloproteases (SVMPs) are a predominant component of viper venoms, and are involved in the degradation of basement membrane proteins (particularly collagen) surrounding the tissues around the bite site. Although their collagenolytic properties have been established, the molecular mechanisms through which SVMPs induce permanent muscle damage are poorly understood. Here, we demonstrate the purification and characterisation of an SVMP from a viper (Crotalus atrox) venom. Mass spectrometry analysis confirmed that this protein is most likely to be a group III metalloprotease (showing high similarity to VAP2A) and has been referred to as CAMP (Crotalus atrox metalloprotease). CAMP displays both collagenolytic and fibrinogenolytic activities and inhibits CRP-XL-induced platelet aggregation. To determine its effects on muscle damage, CAMP was administered into the tibialis anterior muscle of mice and its actions were compared with cardiotoxin I (a three-finger toxin) from an elapid snake (Naja pallida) venom. Extensive immunohistochemistry analyses revealed that CAMP significantly damages skeletal muscles by attacking the collagen scaffold and other important basement membrane proteins, and prevents their regeneration through disrupting the functions of satellite cells. In contrast, cardiotoxin I destroys skeletal muscle by damaging the plasma membrane, but does not impact regeneration due to its inability to affect the extracellular matrix. Overall, this study provides novel insights into the mechanisms through which SVMPs induce permanent muscle damage.